The Productivity of Duck in Different Temperature Cage Management - Nova, Tertia Delia; Syahruddin, Erman; Zein, Rijal (Jurnal Natur Indonesia, 2020)
This study aims to determine the performance of  ducks on the effect of differences in cage temperature. This study used 54 5-week-old male ducks selected from 66 ducks. The research method used was randomized block design (RBD). The treatment used is the regulation of the temperature of the cage which is divided into three temperature levels, namely: A (cold temperature), B (room temperature), and C (hot temperature). The observed variables were duck performance in the form of feed consumption, body weight gain and feed conversion. The results of this study indicate that the difference in temperature of the cage became a very significant (P<0.01) on the consumption of rations, weight gain and conversion. The results of the study concluded that the maintenance of ducks at three different cage temperatures had a very significant (P<0.01) on feed consumption and body weight gain, but had no effect on feed conversion. The best results were found in the temperature of the cold cage with the consumption of rations of 2964.33 g/head, which resulted in body weight of 711.83 g/head of g/head, and conversion of 4.2. While the body weight of 1437 percentage of carcass was 67.64% in the study. The highest yield IOFC results (income over feed cost) cage in cold temperatures with a profit of Rp. 3,375.15/head. The maintenance of  ducks at three different cage temperatures had no significant effect (P>0.05) on the weight of the spleen, thyroid and kidney and the work of the spleen, thyroid and kidney organs was still normal